Des îles et des lunes - Arthur Ségard (Genre, Sexualité et Société)
By analyzing four works of fiction, this article discusses the political uses of queer heterotopias. The works studied showcase counter-spaces, opposing the heteropatriarchal norms supported by disciplinary technologies. As I highlight in this article, the notion of heterotopia, as developed by Michel Foucault, allows us to grasp the connection that these fictional counter-spaces establish between spatiality, imagination and political contestation. These queer heterotopias experiment with alternative identities and practices, as they propose another political organization of the world, and new, freer, more harmonious relationships between beings, bodies and genders. If they often have an ambiguous and precarious dimension, stressed by the works themselves, they can however have concrete political effects, as the fiction interacts with the reader’s affects and social imaginary.